1959
DOI: 10.1002/pol.1959.1203412704
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies on a Ziegler catalyst system

Abstract: Measurements have been made on the kinetics of the polymerization of ethylene using Ziegler‐type catalysts made from zine di‐n‐butyl and titanium tetrchloride in hydrocarbon solvents. The rate of polymerization was proportional to the square of the ethylene pressure. At catalyst ratios (the molar ratio of zine butyl to titanium tetrachoride in the reaction mixture) less than 0.5, an initial, fast polymerzation was followed by a slower but more persistent polymerization. Both processes increased in velocity wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1959
1959
1984
1984

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The combinations of the two components which are active in ethylene polymerization are numberless [60,02]. As organometallic compounds, they have been used, in mixture with TiCl 4 or TiCI 3 , alkyl or hydride derivatives of AI, Li [63], Na [64], K [65], Zn [66,67], Cd [68], Ga [69], and B [70].…”
Section: Ziegler-natta Heterogeneous Catalystsmentioning
confidence: 99%
“…The combinations of the two components which are active in ethylene polymerization are numberless [60,02]. As organometallic compounds, they have been used, in mixture with TiCl 4 or TiCI 3 , alkyl or hydride derivatives of AI, Li [63], Na [64], K [65], Zn [66,67], Cd [68], Ga [69], and B [70].…”
Section: Ziegler-natta Heterogeneous Catalystsmentioning
confidence: 99%
“…Ethylene is polymerized under the influence of titanium (IV) and tetrabutylzine at a rate which is proportional to the square of the ethylene concentration (132). Orzechowski (303) has found that the most efficient catalyst ratio for a mixture of titanium ( 7) chloride and isobutylaluminum is between 1.4 and 2.8 (aluminum: titanium).…”
Section: The Ziegler-natta Type Of Polymerization Catalystmentioning
confidence: 99%
“…For example, Feilchenfeld & Jeselson (1959), in studies with the active complex obtained from aluminium triethyl and titanium tetrachloride, concluded th a t the polymerization is first order with respect to ethylene and to titanium tetrachloride if the alkylating agent is in excess. McGowan & Ford (1958) and Gilchrist (1959) found th at ethylene polymerization with a catalyst composed of titanium tetrachloride and an excess of either lithium butyl or zinc dibutyl was first order in metal halide and second order in monomer. Ludlum, Anderson & Ashby (1958) have investigated the polymerization of ethylene using four different alkylating agents together with titanium tetrachloride as catalysts.…”
mentioning
confidence: 99%
“…The value of this ratio depended upon the nature of the metal alkyl. Kinetic measurements using other a-olefins and diolefins have been made by N atta (1959( ), by N atta & Pasquon (1959 and by Gaylord,Kwei & Mark (i960). These authors have investigated the effects of solvent, temperature and metal alkyl/metal halide ratio on the rates of polymerization and on the pro perties of the polymers.…”
mentioning
confidence: 99%